DECONSTRUCTING NARRATIVE STRUCTURE: A LINGUISTIC FRAMEWORK FOR CT-BASED SHORT STORY WRITING - Sari, Fransiska Marta; Mudhar; Riyati; Utami, Sri (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This research addresses the persistent difficulties students face in developing story ideas, creating interesting plots, describing characters and settings, and composing well-structured sentences. Consequently, these pose learning obstacles in Indonesian short story writing. Although innovative learning methods and technology have been implemented, the fundamental challenge lies in students' abilities to organize ideas logically and structurally in the writing process. This condition is reinforced by the results of the PISA study which indicates that Indonesian students' writing literacy skills are still below the OECD average, indicating the need for a learning approach that focuses not only on linguistic aspects, but also on developing students' cognitive abilities in solving problems and thinking in a structured manner. Computational Thinking (CT) is presented as a potential solution, to be implemented in the story outlining process by breaking down the complex story ideas into smaller parts (decomposition), identifying patterns in narratives (pattern recognition), focusing on important elements (abstraction), and designing structured writing steps (algorithm). This study aims to develop CT-based short story writing skills in elementary school students, hoping to facilitate their systematic application of CT components in the writing process. The Research and Development (R&D) method used in this study comprises the following stages: problem identification, initial data collection, product design, expert validation, design revision, limited trials, product revision, classroom usage trials, final product revision, and dissemination. This study involves 5th grade students of Cita Hati Christian Elementary School. Data were collected through observation, the rubric used for assessing outlines and short stories (in Flipbook format), and student-survey responses after the learning activity. The results of the study showed that the integration of CT in learning materials and the short story writing process had a positive impact on students’ ability to produce more structured and creative writing. Students demonstrated improved short story writing abilities and responded positively to the CT approach in Indonesian language learning. Thus, the development of CT-based learning materials has effectively empowered students to think logically and systematically when planning, composing, and developing their short stories